From Classroom to Community: Enhancing Cultural Competence of Vietnamese Students through Service-Learning Projects - Phan, Thi Ngoc Le (Journal of Ethnic and Cultural Studies, 2025)
Community service-learning is an educational method that creates conditions for students to participate in an organized community activity and then reflect the benefits that activity brings to them. One of the factors to conduct successful community activities is that students need to understand the culture of the local areas where the students come to work on the project. From these perspectives, this research was conducted to explore the effectiveness of service-learning to cultural competence of Vietnamese students. The study involved 30 students, who participated in a community learning project, also known as a project to improve the quality of English teaching and learning in the local provinces. I used quantitative and qualitative methods to collect and analyze data through questionnaires and semi-structured interviews to investigate whether students’ cultural competence would increase or not after participating in community service activities. The results highlighted the feasibility of community service-learning in enhancing students’ cultural competence, especially in aspects such as cultural awareness, cultural knowledge, and cultural desire. From this, I also proposed some solutions for integrating service-learning projects into the curriculum to be appropriate for the current teaching and learning context.